Ire Gbogbo' Polical Rhetoric in Nigeria's 2015 General Elections. An Orunmilast Sociological Perspective (2017)
This paper adopts the valuation of the sociologist as the 'arokun' of the society who applied 'ifongbo t'aiyese', and interrogates the poitical rhetoric used in campaign speeches and write-ups prior to the 2015 general elections along the lines of the common social values encaosulated in the principles of ire-gbogbo (the valve of collectivity), ire oko-aya (the value of good health), ire owo (financial security), ire oko-aya (the value of self-actualization). Akinwowo's varlations in the theme of sociation provide an insightful framework for this paper, which attempts a content analysis of selected rhetorics. the paper argues tht in line with ifongbo t'aiyese grounded in the Orunmilaist sociological perspertive, the social values of ire-gbogbo provides the theoretical foundations for social collectivity and nationhood development, and further highlights albeit theoretically that the failings of politicians to include these core values in their speeches (or their deceptive misuse of them),under develop the nation by bringing upon it diverse forms of social ils.it concludes that Nigeria's development as nation is inhibited by elements of igbinkugbin (sifling alien cultures) such as character assassination,insult-hurling. which are bye-products of the strife laden ajogbe society.